Efektivitas Modul Struktur Atom Berbasis Guided Discovery Learning Terintegrasi TPACK terhadap Peningkatan Kemampuan Literasi Kimia Peserta Didik Fase E di SMA - Alifa, Zaqiya Zahwa; Yerimadesi, Yerimadesi; Iryani, Iryani; Yuhelman, Nofri (Universitas Negeri Padang, 2025)
This study aimed to analyze the effectiveness of the atomic structure module based on guided discovery learning integrated with TPACK on improving the chemical literacy skills of phase E students in high school. The research applied the type of quasi-experiment with pretest-posttest control group design. The population includes phase E students of class X SMAN 1 Sungai Penuh who are studying chemistry in the 2024/2025 academic year, as many as seven classes. Samples were taken using a purposive sampling technique, and the experimental class X.D and control class X.F were selected. Chemical literacy test instrument in the form of essay questions. The data obtained were analyzed using the n-gain test and hypothesis testing with the 't' test. The results of data analysis obtained the n-gain value of the control class and experimental class, respectively, 0.20 in the low category and 0.35 in the medium category. The hypothesis test results obtained tcount > ttable, which is 3.43> 2.009. The chemical literacy ability of the experimental class is significantly higher than that of the control class. So the atomic structure module based on guided discovery learning integrated with TPACK effectively improves the chemical literacy skills of SMAN 1 Sungai Penuh phase E students.